Ownership Structures and Firm Value: Does Firm Size Matter? - Lina (Universitas Pelita Harapan, 2025)
This study aims to empirically demonstrate the positive influence of managerial and institutional ownership on firm value. Furthermore, it aims to demonstrate the moderating role of firm size in strengthening this relationship. This study used a sample of mining companies listed on the Indonesia Stock Exchange for the 2019-2023 period. This study successfully demonstrated that managerial and institutional ownership have a positive effect on firm value. However, the results failed to demonstrate the role of firm size in strengthening the positive influence of managerial and institutional ownership on firm value.